Haploid induction in spring onion (Allium fistulosum L.) via gynogenesis - Ahmed Mahmood Ibrahim; Fatimah Kayat; Dwi Susanto; Pedram Kashiani; Mohammed Arifullah (Asian Network for Scientific Information, 2016)
Regeneration into haploid plantlets had been obtained in spring onion using flower and ovary culture. Flowers and ovaries were cultured into media using two protocols (A and B) and the ability to produce callus or somatic embryogenesis were invistigated. Flowers around 3.0-5.0 mm long were collected, whole flower or ovary which were excised from flowers using dissecting microscope were cultured into BDS medium supplemented 2.0 mg L⁻¹ 2, 4-D and 2.0 mg L⁻¹ myo-inositol (protocol A) or into BDS media supplemented 2.0 mg L⁻¹ BAP fortified with 100 g L⁻¹ 2,4-0 and 2.0 mg L⁻¹ sucrose, 200 mg L⁻¹ BAP for 14 days, then sub-cultured by regeneration medium (BDS) supplemented with 1.0 mg L⁻¹ NAA and 2.0 mg L⁻¹ 2iP (protocol B). Embryos were emerged from ovary wall after around 4-5 months, high frequency of embryogenesis induction was produced from ovaries that were using protocol A. While the less percentage observed from flower culture using protocol B.